Addendum: Analysis of game variables and influence on defensive success in elite handball - Iván González-García (CV Rezki Media, 2025)
This addendum provides additional statements on informed consent, data availability, and AI disclosure to enhance transparency and align the original article with current international publication standards. These updates do not affect the results, interpretation, or conclusions of the original publication.